2020
DOI: 10.4103/meajo.meajo_237_20
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and recommendations for tonometry use during the COVID-19 era

Abstract: The novel coronavirus disease COVID-19 caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has resulted in a substantial change in eye care and clinical practice. There has been conflicting information and weak evidence on the virus's transmission through tears. Yet, virus detection on cornea and conjunctiva surface as a gateway for infection is not well-studied. Moreover, there have been no reported cases of SARS-CoV-2 transmission through tonometry to date. Thus, this uncertainty has urged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…Although sodium hypochlorite is a likely disinfectant for prisms, disposable prisms are recommended when performing Goldmann applanation tonometry when possible. 46 Equipment and surfaces should be disinfected with a virucidal agent in between each patient examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although sodium hypochlorite is a likely disinfectant for prisms, disposable prisms are recommended when performing Goldmann applanation tonometry when possible. 46 Equipment and surfaces should be disinfected with a virucidal agent in between each patient examination.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison studies between three NTC devices showed that, when taking GAT as the gold standard and aiming to detect IOP > 21 mmHg, sensitivities greatly differed from 40%, 48% and 80%, which showed that NCT readings are device dependent and that devices require regular calibration [ 38 ]. Although NCT offers a non-contact mode of measuring that limits the risk of infection due to contaminated drops or Goldmann prisms, the risk of air-borne infection could be greater considering the air-puff nature, which should be considered in the midst of the recent COVID era [ 42 , 43 , 44 , 45 ].…”
Section: Non-contact Tonometry (Air-puff Tonometry)mentioning
confidence: 99%
“…Unlike adenovirus and herpes simplex virus 1, SARS-CoV-2 transmissibility via the ocular surface remains equivocal [ 36 ▪ ]. Nonetheless, glaucoma practices have widely adopted the use of disposable diagnostic instruments during the pandemic to avoid potential contamination [ 37 ▪ 39 ▪ ].…”
Section: Improving Glaucoma Carementioning
confidence: 99%
“…In a survey of the American Glaucoma Society membership conducted prior to the pandemic, 98% (193 of 197) of glaucoma specialists preferred GAT over other methods of IOP measurement, and 55% (109 of 197) were exclusively using single-use disposable GAT tips [ 41 ▪ ]. Disposable GAT tips are available from multiple manufacturers (Tonosafe, Haag-Streit, Bern, Switzerland; Tonomate, Keeler, Ltd, Windsor, UK; Tonoclear, Keeler, Ltd, Windsor, UK; Tonojet, Luneau, Pont-de-l’Arche, France) and are cost-effective considering the additional expense associated with disinfecting reusable GAT tips [ 36 ▪ ]. Disposable GAT tips demonstrate reasonable correlation with reusable GAT tips for IOP within the normal range [ 42 44 ] and are more reliable than alternative methods of contact tonometry, including Icare (Icare Finland Oy, Vantaa, Finland) and Tono-Pen (Reichert, Inc., Buffalo, New York, USA) [ 44 ], which employ disposable probes and tip covers, respectively.…”
Section: Improving Glaucoma Carementioning
confidence: 99%